Evidence for the essential role of Helicobacter pylori in gastric ulcer disease. Issue 1 (January 1994) - Labenz, J; Börsch, G
Abstract : Helicobacter pylori (H pylori) eradication heals chronic active type B gastritis and dramatically changes the natural history of duodenal ulcer disease. There are few data concerning the role of anti-H pylori treatment in gastric ulcer disease. A total of 83 patients presenting with H pylori positive active gastric ulcer disease were treated with omeprazole and antibiotics (amoxicillin, ciprofloxacin, roxithromycin) in seven different clinical protocols, each of which included the attempt to eradicate H pylori infection and to evaluate the post-therapeutic course of ulcer disease. The overall proportion of H pylori eradication was 67.9% (53 of 78 patients available for follow up). Best results were obtained with two week treatment regimens comprising omeprazole 20 mg twice daily and amoxicillin 500 mg four times a day or 1000 mg twice daily (eradication > 80%). Eradication of H pylori speeds up ulcer healing, with a six week healing rate of 84.9% compared with 60% in patients with persistent H pylori infection (p = 0.0148). In a subgroup of 11 patients with refractory ulcers, H pylori eradication (n = 10) was associated with ulcer healing on continued acid suppression in nine cases. One male patient with chronic antral ulcer did not respond to treatment within the next six months (H pylori and ulcer persistence), and in one female patient a resistant body ulcer was identified as gastric lymphoma. Fifty patients with healed ulcers were followed up for one year. Patients with (n = 32) and without (n = 18) bacterial eradication had similar demographic and clinical characteristics. H pylori eradication was associated with a statistically significant reduction of ulcer recurrences (3.1 v 55.6%, p<0.001). This study concludes that H pylori eradication considerably changes the natural history of H pylori associated gastric ulcer disease. In addition, H pylori eradication speeds up ulcers healing and is associated with healing of previously refractory ulcers. Thus, treatment aimed at bacterial eradication should be considered in all patients with gastric ulcers severe enough to contemplate further treatment options.